Solar Radiation and Daylighting Assessment Using the Sky-view Factor (SVF) Analysis as Method to Evaluate Urban Planning Densification Policies Impacts. (June 2016) - López, Cristina S. Polo; Sala, Mariaemma; Tagliabue, Lavinia Ch.; Frontini, Francesco; Bouziri, Salim
Abstract: This study identifies and proposes simple methods to assess solar radiation, daylighting availability and Sky-View Factor (SVF) modification, in complex urban environment. Numerical methods and 3D simulation software are combined with photo processing methods using digital cameras with special mirrors to project the hemispherical environment onto a circular image. This methodology has been applied to a real case study in Switzerland that is undergoing a very fast urban densification process, where urban planning strategies will determine significantly the possibility to relish solar irradiation in buildings. This paper analyzed the particularities of different urban scenarios considering the effects of urban densification planning strategies on existing buildings, in particular historical protected buildings.